Research on Wind Resistance Optimization Method for Cable-Stiffened, Single-Layer Spherical Reticulated Shell Based on QPSO Algorithm - Zhao, Ying; Chen, Guohan; Song, Shushuang; Huang, Mingyao; Zhang, Tianhao; Li, Pengcheng; Xiong, Gang (Buildings, 2024)
This study proposes an improved mixed-variable quantum particle swarm optimization (QPSO) algorithm capable of optimizing both continuous and discrete variables. The algorithm is applied to the wind resistance optimization of a cable-stiffened, single-layer spherical reticulated shell (SLSRS), optimizing discrete variables like member dimensions and cable dimensions alongside continuous variables such as cable prestress. Through a computational case study on an SLSRS, the optimization results of the proposed QPSO method are compared with other optimization techniques, validating its accuracy and reliability. Furthermore, this study establishes a mathematical model for the wind resistance optimization of cable-stiffened SLSRSs and outlines the wind resistance optimization process based on the mixed-variable QPSO algorithm. The optimization of these structures reveals the strong stability and global search capabilities of the proposed algorithm. Additionally, the comparison of section optimization and shape optimization highlights the significant impact of the shell shape on steel usage and costs, underscoring the importance of shape optimization in the design process.